'La Otra', en el imaginario cristiano plenomedieval : la mujer musulmana asociada a la lujuria en el arte románico - Monteira Arias, Inés (My University, 2013)
‘La Otra’ (The Other) in Medieval Christian Imagery: the Muslim woman as an emblem of lust in Romanic art Under the moral order of the medieval ecclesiasts, lust proliferated as a theme in Romanic sculpture. It was generally represented by feminine figures. Women were viewed as embodying this sin in accordance with the misogyny of monastic thinking. This article examines both the representation of the woman who presents her sexual organ and the twin-tailed fish-siren, both sometimes used to represent the Muslim woman. The veil is characteristic of these figures and identifies them as representations of the ‘Saracens’. Analysis of contemporaneous texts demonstrates the systematic association of ‘sins of the flesh’ with religious rivals. This emphasis on the alterity of Christian and Muslim, and the creation of false and discriminatory representations, fueled the Christian ideology that framed war as Holy War. The ‘infidel’ woman was represent ‘sins of the flesh’ in Christian Europe in an especially emblematic way, coupling their religious otherness with their female gender. When these ‘Saracens’ appear in epic poems and in Romanic sculpture they symbolize religious otherness with great visual impact. They transmit an opportunistic, moralizing message in the war context (‘Reconquest’ and crusades), and became a powerful ideological instrument for the sacralization of the war against Islam.
Keywords: Kunst; Christentum; Islam; 700 Künste; Mittelalter